FACTORAL ASSESSMENT OF ENERGY-EFFECTIVE CONSTRUCTIVE- TECHNOLOGICAL SOLUTION OF THE THERMOPROFILE FROM THE LSTК (Collection of scientific works «Modern structures of metal and wood», 2019)
The features and advantages of innovative structural and technological solutions in construction based on lightweight metal structures are discussed there in the article. The problems of energy- and resource-saving in Ukraine are revealed. Investigations  of  the  main  energy  problems  of  Ukrainian  cities  are  presented  through  the example of Odessa. The spacial layout and structural features of the cottage estate project in Leski village are also described here.  The necessity of applying the methodology of factor evaluation in the  optimization  of  structural  and  technological  solutions  of  cottage  building  frame  assembly  is substantiated taking into consideration the energy efficiency. There are also presented the results of optimization  of  structural  and  technological  solutions.  Theку  are  specified  two  main  factors affecting the choice of architectural, structural and technological solutions for the frame assembly: quantitative and qualitative. Qualitative criteria include: the possibility of year-round installation; ecological compatibility; fire safety. Quantitative  criteria  include:  cost  of  construction;  minimum  wall  thickness  (excluding insulation); frost resistance; sound insulation; duration of construction; operational life; coefficient of thermal conductivity. In the process of selecting alternatives and determining criteria, the communicative individual method is used - when decision options are generated by a single expert. Based  on  the  data  of  factors  evaluation,  on  a  5-point  scale,  the  Light  steel  thin-walled structures technology scored the highest number of points - 67 points, the smallest - silicate brick - 37  points;  it  is  evidence  that  solution  of  the  Light  steel  thin-walled  structures  shows  the  best performance. There  are  proposed  some  ways  for  solving  the  downsides  of  the  Light  steel  thin-walled structures, such as the formation of thermal bridges, which can be reduced in two ways: by using of double frames or external heat insulation systems; ensuring the building tightness in relation to the wind, to the air and to the steam migration through the structure by the obligatory installation of wind protection and a vapor barrier; increasing the fire resistance limit of the Light steel thin-walled structures is provided in one of the ways: spraying and painting with various fire-resistant materials; plasterboard cladding; plastering.